Impact of repeat human leukocyte antigen mismatches on kidney graft survival: a contemporary Collaborative Transplant Study analysis - Pipeleers, Lissa; Unterrainer, Christian; Emonds, Marie-Paule; Wissing, Karl Martin; Tran, Thuong Hien (American journal of transplantation, 2025)
Repeat human leukocyte antigen (HLA) mismatches (RMM) have been historically associated with an increased risk of graft loss after repeat kidney transplantation, in particular HLA-DR RMM in sensitized recipients. As routine use of sensitive assays can at present prevent the transplantation of RMM in hosts with donor-specific antibodies, we hypothesized that RMM would no longer be associated with graft loss. We performed a registry analysis of the Collaborative Transplant Study database including 6711 patients who received a second kidney transplant (KT) between 2010 and 2021, with at least 1 HLA-A, HLA-B, or HLA-DR mismatch. No increased risk for graft loss was observed for the second KT with a class I RMM, regardless of sensitization status. For the second KT with a HLA-DR RMM, the hazard ratio for graft loss in the first year after transplantation was 1.61 (95% CI 1.16-2.23; P = .004) compared to recipients without an RMM and increased to 2.21 (95% CI 1.24-3.63: P = .002) in sensitized recipients (latest complement-dependent cytotoxicity panel reactive antibodies >0%). Our observations suggest that class I RMM do not need to be systematically avoided. In contrast, HLA-DR RMM still had a negative impact on graft survival in this contemporary cohort, despite the widespread availability of Luminex.